2015
DOI: 10.1177/1759720x15580903
|View full text |Cite
|
Sign up to set email alerts
|

Odanacatib: a review of its potential in the management of osteoporosis in postmenopausal women

Abstract: Odanacatib is a cathepsin K inhibitor developed for the treatment of postmenopausal osteoporosis. It is a bone resorption inhibitor, but which preserves bone formation to some extent. It can be administered once a week, in tablets also containing vitamin D. In a large clinical development program, it has been shown that odanacatib reduces bone resorption, with a reduction of about 60-70% in biochemical markers of resorption, while bone formation decreases to a lesser magnitude. Odanacatib continuously increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 51 publications
1
22
0
1
Order By: Relevance
“…Therefore, novel agents have been pursued to mitigate osteolysis induced by breast cancer metastasis. Cathepsin K inhibitor odanacatib has been reported to be an agent against osteoporosis and breast cancer‐induced bone metastasis . However, odanacatib was withdrawn from the clinical trials for safety reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, novel agents have been pursued to mitigate osteolysis induced by breast cancer metastasis. Cathepsin K inhibitor odanacatib has been reported to be an agent against osteoporosis and breast cancer‐induced bone metastasis . However, odanacatib was withdrawn from the clinical trials for safety reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Cathepsin K inhibitor odanacatib has been reported to be an agent against osteoporosis and breast cancer-induced bone metastasis. 22,23 However, odanacatib was withdrawn from the clinical trials for safety reasons. In addition, clinical studies of c-Src inhibitors have been initiated in patients with bone metastases, since c-Src plays multiple roles in the bone resorption and in the proliferation, survival, metastasis of breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that the treatment-related responses of bone resorption markers were similar for CatKI and the typical bisphosphonate alendronate (ALN); however, the reduction in the levels of bone-formation markers was less with CatKI than with ALN26. Moreover, CatKI was generally well tolerated without bone necrosis27. Thus, CatK is considered an important target for the treatment of postmenopausal osteoporosis28.…”
mentioning
confidence: 99%
“…The pros for this decision were the relatively selective expression of CatK in osteoclasts, its proven role as the therapeutically relevant bone collagen‐degrading protease without affecting osteoclast viability when inhibited, and acting as the final executioner in the bone resorption pathway with the promise of fewer side effects than expected when targeting upstream, more complex regulatory proteins such as tumor necrosis factor‐α (TNF‐α) or receptor activator of NF‐κB ligand (RANKL). However, despite the successful generation of potent, selective, and preclinically active CatK inhibitors, and despite the fact that human osteoporosis trials showed impressive bone‐preserving efficacies of CatK inhibitors and keeping bone formation mostly unaffected, none of these compounds were ever approved. Relacatib, balicatib, odanacatib (ODN), and ONO‐5334 were all terminated because of increased side effects or for marketing reasons .…”
Section: Introductionmentioning
confidence: 99%